67Ga-Citrate Accumulation by Staphylococcal Abscesses and by Tumors - Anghileri, Leopoldo J. (Nuklearmedizin - NuclearMedicine, 1974)
The in vivo uptake of 67Ga-citrate by staphylococcal abscesses in rats has been studied. The high accumulation of calcium and magnesium in the abscess and in the surrounding tissues appears to be responsible for the accumulation of 67Ga. The role of the mast cells in the inflammatory process which leads to a calcification (calciphylaxis) is discussed and related to their possible involvement in the case of tumor transplants.